Deathgame - Dixon, Franklin W. (New York : Pocket Books, 1987)
Their friend Biff Hooper's disappearance at a survival game camp in Georgia leads the Hardy boys to discover a training site for an elite corps of attack troops.
An Archway paperback.
Koleksi sumbangan Prof. Dr. Ding Choo Ming.
Keywords: Mystery -- Fiction; Detective and mystery stories; Young adult fiction